Charting a new course for translator and interpreter training in Africa: Lessons from the COVID-19 experience in selected countries - Segun Afolabi; Oludamilola I. Oyetoyan (JoSTrans: The Journal of Specialised Translation)
Translator and interpreter (T&I) training, using virtual learning environments, was largely uninterrupted by the COVID-19 pandemic lockdown in the Global North. This might not have been the case in the Global South, especially in African countries. Building on earlier studies which focused on a comparative analysis of a number of T&I programmes in Africa, the objective of this paper is to further investigate the T&I training situation in a number of African countries between the pre-COVID-19 (before March 2020) and the initial lockdown (March - September 2020) period. Online questionnaires were administered to T&I students and trainers in five countries: Benin, Cameroon, Nigeria, Senegal, and Togo. The data collected were analysed qualitatively. Our preliminary findings, although not surprisingly, reveal that T&I training was interrupted by the lockdown and the attempted transition to online teaching and learning has not been smooth, due to economic challenges, insufficient technological infrastructure and skilled human resources. We find that the provision of reliable technological facilities and the implementation of blended learning are essential for strategic development in African T&I training. Trainers also require continuous professional development to enable them to acquire technological and pedagogical skills necessary to provide training that meets current T&I market demands.